QUANTITATIVE EASING AND ITS EFFECTS ON ASSET PRICES (International Journal of Food and Nutritional Sciences, 2022)
Quantitative Easing (QE) has emerged as a critical monetary policy tool employed by central banks to stimulate economic activity during periods of financial crisis or economic stagnation, particularly when conventional policy tools, such as short-term interest rate reductions, are insufficient. QE involves large-scale purchases of financial assets, primarily long-term government bonds and mortgage-backed securities, by central banks with the aim of injecting liquidity into the financial system, lowering long-term interest rates, and encouraging lending and investment. Since the global financial crisis of 2008, QE has been implemented extensively by major central banks, including the United States Federal Reserve, the European Central Bank, the Bank of England, and the Bank of Japan.The implementation of QE has had profound and widespread effects on asset prices across various financial markets. By reducing yields on government bonds and other traditionally safe investments, QE has encouraged investors to reallocate their capital into riskier assets such as equities, corporate bonds, real estate, and commodities, leading to significant increases in the prices of these assets. This phenomenon, often referred to as the "portfolio rebalancing effect," has contributed to prolonged stock market rallies, housing price inflation, and a general rise in the valuation of financial and real assets globally.While QE has been effective in stabilizing financial markets, boosting investor confidence, and supporting economic recovery in the short term, its broader effects on asset prices have also sparked concerns about the creation of asset bubbles, growing wealth inequality, and the distortion of market fundamentals. Moreover, unwinding QE, known as quantitative tightening, presents significant challenges for policymakers seeking to maintain financial stability without triggering abrupt declines in asset prices. This paper explores the mechanisms through which QE influences asset prices and critically examines the positive and negative consequences of this widely used monetary policy tool.